2017
DOI: 10.1093/geronb/gbx104
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Old-Age Public Transfer on the Well-Being of Older Adults: The Case of Social Pension in South Korea

Abstract: Our findings contrast with those from the literature. The Korean literature fails to find positive effects on the well-being of older persons. The literature of other countries finds negative incentive effects. The discrepancy may result from differences in methodological approaches and social and cultural contexts and institutional characteristics of the social pension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 22 publications
0
29
1
Order By: Relevance
“…The fact that the program was implemented near the peak of the 2007-2008 financial crisis raises the possibility that the recession may have affected poor seniors to a greater extent and through this pathway partially offset the correlation between the BOAP and beneficiaries' financial condition. Indeed, recent research on the 2014 reform demonstrated a declining poverty gap and a significant rise in consumption expenditures and subjective well-being among those who benefited from the reform (Lee et al, 2019;Pak, 2020a;2020b). We extend this line of research by examining whether the 2014 reform had a spillover effect on health outcomes.…”
Section: Basic Old-age Pension In South Koreamentioning
confidence: 80%
See 1 more Smart Citation
“…The fact that the program was implemented near the peak of the 2007-2008 financial crisis raises the possibility that the recession may have affected poor seniors to a greater extent and through this pathway partially offset the correlation between the BOAP and beneficiaries' financial condition. Indeed, recent research on the 2014 reform demonstrated a declining poverty gap and a significant rise in consumption expenditures and subjective well-being among those who benefited from the reform (Lee et al, 2019;Pak, 2020a;2020b). We extend this line of research by examining whether the 2014 reform had a spillover effect on health outcomes.…”
Section: Basic Old-age Pension In South Koreamentioning
confidence: 80%
“…Moreover, studies have disagreed as to whether the BOAP reduced labor supply and to what extent replaced private transfer from adult children to parents. Lee et al (2019) found no changes in labor income and private transfer income after the 2014 reform, while Lee and Lee (2009) found a moderate correlation between the BOAP and private transfer among middle-income families.…”
Section: Basic Old-age Pension In South Koreamentioning
confidence: 88%
“…The South Korean government introduced the basic old-age pension in January 2008 and doubled its monthly allowance in July 2014 (Lee 2017). The expansion in 2014 was one of the largest social welfare reforms in South Korean history (United Nations ESCAP 2015) and provides an excellent opportunity to isolate exogenous increase in pension benefits (Lee, Ku, and Shon 2019). Our empirical model examines changes in travel frequency and expenditures before and after the 2014 reform among eligible persons, in comparison to noneligible individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Studies analyzing the impact of social security schemes often use difference-indifference (DD) or regression discontinuity (RD) design methods [2]. We used a DD model to control for pre-policy characteristics and to estimate the policy effect of the BOP on The DD model compares the changes in the beneficiaries and non-beneficiaries in the pre-and post-policy periods.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the BOP reduced the poverty rate of older adults [ 1 ]. The most recent study, by Lee et al [ 2 ], conducted a comprehensive analysis of the effects of introducing the Basic Pension, an upgraded version of BOP in 2014, including on total consumption, non-consumption expenditures, poverty rate and poverty gap. They used a more sophisticated methodology than that of previous studies, but still focused only on material wellbeing.…”
Section: Introductionmentioning
confidence: 99%